Rancangan dan Implementasi Aplikasi Web Point of Sales pada Butik Anak “Galery Freya” - Muhammad Sony Maulana (Universitas Bina Sarana Informatika, 2017)
ABSTRACTThis study aimed to design and implement an application point of sales on children's boutique